1997
DOI: 10.1021/jf960648o
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Esterase and Alcohol Acetyltransferase on Production of Isoamyl Acetate in Hansenula mrakii

Abstract: Isoamyl acetate is a major determinant of the quality of Japanese sake. The amount of isoamyl acetate in the cultures of Hansenula mrakii and Saccharomyces cerevisiae Kyokai No. 7, which is industrially used in sake fermentation, and the isoamyl acetate-producing activities of each yeast strain were compared to investigate biochemical properties of the producing system of isoamyl acetate in these yeast strains. S. cerevisiae could not produce, or produced an extremely low level of, isoamyl acetate when the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 24 publications
1
48
0
1
Order By: Relevance
“…Williopsis yeasts are not usually associated with beer fermentation, but have found potential applications in wine and sake fermentations (12)(13)(14). Furthermore, the ability of Williopsis yeasts to produce esters, especially acetate esters, while producing small amounts of ethanol in wine suggests a feasible way for production of fruity, low-alcohol beer (14).…”
Section: Evaluation Of Beer Fermentation With a Novel Yeast Williopsimentioning
confidence: 99%
“…Williopsis yeasts are not usually associated with beer fermentation, but have found potential applications in wine and sake fermentations (12)(13)(14). Furthermore, the ability of Williopsis yeasts to produce esters, especially acetate esters, while producing small amounts of ethanol in wine suggests a feasible way for production of fruity, low-alcohol beer (14).…”
Section: Evaluation Of Beer Fermentation With a Novel Yeast Williopsimentioning
confidence: 99%
“…The OAVs of acetate esters were much higher in the monoculture of W. mrakii (Table 2), but excess amount of acetate esters could impart offflavour (JACkSon, 2000). In S. cerevisiae, alcohol acetyl-transferase (AATase) was labile (Minetoki, 1992), but it was stable in W. mrakii (Inoue et al, 1997). Acetate ester hydrolyzing enzyme in S. cerevisiae is activated when it is in mixed-culture (KuritA, 2008).…”
Section: Evolution Of Volatilesmentioning
confidence: 99%
“…W. mrakii, formerly known as Hansenula mrakii, is an efficient producer of acetate esters (Li et al, 2012). The yeast has been inoculated to improve the fruity character of Japanese sake (Inoue et al, 1997), grape wine (Erten & TAnguLer, 2010) and papaya wine (Lee et al, 2010). This research is to assess the influence of S. cerevisiae and W. mrakii as both mono-and mixedcultures on mango wine characteristics.…”
mentioning
confidence: 99%
“…Esterases are expressed in yeast strains used for alcoholic beverage production and their involvement in affecting the aroma of such beverages has been the subject of several studies. By regulating the equilibrium between esters and free acids, esterases might determine ester synthesis 3,12,20,23,25 , but seem to be mainly involved in their breakdown 6,8,12 . For example, isoamyl acetate, which is thought to be synthesized from isoamyl alcohol and acetyl CoA by yeast alcohol acetyltransferase, is hydrolyzed by yeast esterases in sake mash 7,8 thus affecting the flavour quality of this beverage.…”
Section: -2863(9'8-32mentioning
confidence: 99%
“…Moreover, it has been reported that esterases present in the soluble cell fractions of the yeast Hansenula mrakii have some ester-synthesizing activity, and the ester-hydrolyzing activity was detected in both the soluble and insoluble cell fractions 12 , indicating different actions of the esterases belonging to the different parts of the yeast cell. From this point of view, the characterization of the different yeast esterases is of primary importance and the methods described here for the fractionation and visualization on gels of these enzymes contribute to a better understanding of their action.…”
Section: (Ixigxmsr Sj Iwxivewi Egxmzmx] Sr Ipigxvs Tlsvixmg Kipwmentioning
confidence: 99%